Anglicisms In Spanish Dictionaries - Uktamova Malika Khasanovna (Zien Journals, 2021)
This paper compares and contrast the results of the borrowing process in the previous era (on the material of Anglicisms) and at the present time (on the material of Anglicisms) in order to identify their features, as well as synchronous analysis of specific linguistic facts in the field of borrowing, taking into account diachrony data and the definition of general patterns and trends of foreign language lexemes in the process of their real functioning, as well as the study of the qualitative and quantitative composition of borrowed vocabulary, ways of entry of English borrowings into the Spanish language
Keywords: Anglicisms; borrowed vocabulary; Spanish language; synchronous analysis